In vitro assessment of the impacts of leaflet design on the hemodynamic characteristics of ePTFE pulmonary prosthetic valves - Zhu, Guangyu (2020)
Prosthetic pulmonary valves are widely used in the management procedures of various congenital heart diseases, including the surgical pulmonary valve replacement (PVR) and right ventricular outflow tract reconstruction (RVOT). The discouraging long-term outcomes of standard prostheses, including homografts and bioprosthetic, constrained their indications. Recent developments in the expanded-polytetrafluoroethylene (ePTFE) pulmonary prosthetic valves provide promising alternatives. In this study, the hemodynamic characteristics of bileaflet and trileaflet ePTFE valve designs were experimentally evaluated. The in vitro tests were performed under the right ventricle (RV) flow conditions by using an in vitro RV circulatory system and particle image velocimetry (PIV). The leaflet kinetics, trans-valvular pressure gradients, effective orifice areas, regurgitant fractions, energy losses, velocity fields, and Reynolds shear stress (RSS) in both prostheses were evaluated. The opening of the bileaflet and trileaflet valve takes 0.060 and 0.088 s, respectively. The closing of the former takes 0.140 s, in contrast to 0.176 s of the latter. The trans-valvular pressure is 6.8 mmHg in the bileaflet valve vs. 7.9 mmHg in the trileaflet valve. The effective orifice area is 1.83 cm2 in the bileaflet valve and 1.72 cm2 in the trileaflet valve. The regurgitant fraction and energy loss of bileaflet are 7.13% and 82 mJ, which are 7.84% and 101.64 mJ in its bileaflet counterpart. The maximum RSS of 48.0 and 49.2 Pa occur at the systole peak in the bileaflet and trileaflet valve, respectively. A higher average RSS level is found in the bileaflet valve. The results from this preliminary study indicate that the current bileaflet prosthetic valve design is capable of providing a better overall hemodynamic performance than the trileaflet design.